Keunggulan bahasa Al-Qur’an di bidang balaghah - Kulsum, Umi (Maliki Interdisciplinary Journal, 2023)
In the view of the Arabs, it is important for them to understand the text of the Qur'an in order to improve their understanding of language and gain good linguistic sensitivity. Therefore, the development of knowledge about the language of the Qur'an has made a significant contribution to the growth and development of Arabic language and literature. One of the commentators who has a strong interest in studying the language and literature of the Qur'an is Ibn Asyur. The interpretation approach taken is to describe the features of the Qur'an (I'jaz al-Qur'an) with a large focus on the linguistics and literature contained therein. In this paper, several matters related to language and literature (al-balaghah) in the Qur'an will be discussed. First, it will be explained how the Qur'an has a unique language dialectic. Next, we will explain the meaning of 'ilm al-balaghah in this context. Finally, Ibn Asyur's views on the superiority of the Qur'an in the field of literature (al-balaghah) will be presented. To get solutions to some of the problems described above, the author uses a descriptive-analytic approach in this paper. Presentation of information is done by describing in detail, then analyzed, and ends with a conclusion. In research on the language and literature of the Qur'an according to Ibn Asyur, there are several findings that can be explained as follows: (1) The style of the language of the Qur'an is different from the standard Arabic style because it reflects a unique dialectic; (2) The science of al-balaghah is the science that explains how the sentences in the Qur'an are adapted to the situation and the listener to which the utterance is intended; (3) According to Ibn 'Asyur, the language of the Qur'an is a form of Arabic which has a very high literary quality when compared to everyday Arabic. Because the contents of the Qur'an use subtle words and have their own impression that exceeds the ability of human language.